2014
DOI: 10.1098/rspa.2014.0463
|View full text |Cite
|
Sign up to set email alerts
|

Variable tilt on lipid membranes

Abstract: A continuum theory for lipid membranes is developed that accounts for mechanical interactions between lipid tilt and membrane shape. For planar membranes, a linear version of the theory is used to predict tilt variations similar to those observed in experiments and molecular dynamics simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Further, our model accounts for the elastic free-energy of the edge of open lipid bilayers in which the lipid molecules are tilted only at the edge, forming a semicylindrical rim along it. Another generalization of the present work would include tilt fields of smaller gradient, such as those considered by Hamm and Kozlov [45], Rangamani and Steigmann [46], and Rangamani et al [47]. In such an approach, the gradual tilt at the vicinity of the edge changes the thickness of the lipid bilayer and, thus, leads to the deviation of the conformation of the edge from a semicylindrical shape.…”
Section: Discussion and Summarymentioning
confidence: 89%
See 1 more Smart Citation
“…Further, our model accounts for the elastic free-energy of the edge of open lipid bilayers in which the lipid molecules are tilted only at the edge, forming a semicylindrical rim along it. Another generalization of the present work would include tilt fields of smaller gradient, such as those considered by Hamm and Kozlov [45], Rangamani and Steigmann [46], and Rangamani et al [47]. In such an approach, the gradual tilt at the vicinity of the edge changes the thickness of the lipid bilayer and, thus, leads to the deviation of the conformation of the edge from a semicylindrical shape.…”
Section: Discussion and Summarymentioning
confidence: 89%
“…It was demonstrated in the previous section that when the spheroidal interaction potential [27] is employed in the microphysical model, the spontaneous curvatures κ g• and κ n• , and the coefficient k 5 vanish, while the bending moduli k 1 and k 2 find the same value. Using those results in (46) yields…”
Section: Illustrative Example: Dependence Of Freeenergy On the Pore Sizementioning
confidence: 97%
“…Cell surface receptors, linkers, enzymatic proteins, and proteins responsible for cell adhesion [66] are all classes of integral membrane proteins and hormone receptors, Band3, rhodopsin, histocompatibility antigens, glycophorin, and Na + and K + channels are some examples of integral proteins in a cell membrane. Recent studies have shown that activity of these proteins depends on the lipid composition and membrane-protein interactions more so than previously thought [79,80], highlight the role of lipids in the activity of these molecules fundamental for biological information transfer [81][82][83].…”
Section: Integral Proteinsmentioning
confidence: 94%
“…∇ → z 0) as approaching the boundary. In particular, the unknown potential ξ η H q ( , , ) can be expressed as 40 The detailed procedures which can be found in [29][30][31] where μ λ = k 2 / is the natural length scale which is commonly adopted in the membrane studies (see, for example 11,14,25 ). Details regarding the dimensionless variables adopted in the present work will be discussed in later section.…”
Section: Solutions To the Linearized Systemsmentioning
confidence: 99%
“…In the present study, we assimilate data under the normalized setting using the aforementioned values. The dimensionless parameters used in the simulations are adopted from the works 11,14,25 as;…”
Section: Solutions To the Linearized Systemsmentioning
confidence: 99%